PENGARUH EFEKTIVITAS KOMITE AUDIT TERHADAP FINANCIAL REPORTING LEAD TIME - Yosefina Rossa Safira; Moh Didik Ardiyanto (Diponegoro Journal of Accounting, 2018)
This study aims to examine the effect of audit committee effectiveness to financial reporting lead time. The independent variable that is used in this research is measured by an index based on the framework developed by DeZoort et al (2002) such as composition, authority, resources dan diligence. The dependent variable that is used in this research is financial reporting lead time.The population consist of non financial companies listed on Indonesia Stock Exchange 2016. Samples are selected using purposive sampling method and acquired 209. Test analysis using multiple regression model.Finding in this study indicates that authority and diligence influences negative significant to financial reporting lead time. Composition is not influences significant to financial reporting lead time and resources influences positively significant to financial reporting lead time. This matter is indication that the audit committee authority and diligence can reduce the financial reporting lead time so it will assist the investor in valuations of company performance and can conduct the correct analysis regarding the company prospect in the future.